Perancangan Program Aplikasi Deteksi Iris Mata untuk Absensi Karyawan Menggunakan Metode Gabor Wavelet - Zahedi Zahedi; Eka Janitra (ComTech: Computer, Mathematics and Engineering Applications, 2011)
To take the employees’ absences in a company, a variety of invented tools or technologies are and already used, for example, attendance cards, fingerprints attendance tool, and attendance tool that uses facial recognition. Attendance tool with a facial recognition uses iris recognition of those employees. Iris code has many properties that hard to forge. Thus, the detection and iris recognition is one of the most secure and accurate for identification.